PENGARUH FIRM SIZE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Angga Pratama, AA. Bagus; Wiksuana, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The purpose of this study is to determine the significance of Firm Size, Profitability, and Capital Structure to Corporate Value and to know the significance of Firm Size and Profitability influence on Capital Structure. This research was conducted at Consumer Goods Industry Company which listed in BEI period 2012-2016, using purposive sampling method with total sample of 24 companies. Data collection method used is non participant observation method. This research uses path analysis technique (path analysis). Based on the results of the analysis that has been done concluded that Firm Size and Capital Structure have a significant positive effect on Corporate Value. While Profitability has a significant negative effect on Corporate Value. Other results conclude Firm Size has a significant positive effect on Capital Structure. While Profitability have significant negative effect to Capital Structure. Capital Structure is able to mediate the influence of Firm Size on Corporate Value. Capital Structure is not able to mediate the effect of Profitability on Corporate Value.